Sequential signalling under a peak power constraint - Schalkwijk, J.; Barron, M. (IEEE transactions on information theory, 1971)
The error exponent for sequential signaling over the additive-Gaussian-white-noise channel subject to a peak power constraint is derived. This exponent is maximum under the assumption that information is transmitted in blocks.